Description of the larva of Simulium lobatoi Luna Dias, Hernandez, Maia-Herzog & Shelley (Diptera: Simuliidae) from Brazil - Hernández, Luis Miguel; Hamada, Neusa; Pepinelli, Mateus; Kikuchi, Regina Mayumi (Zootaxa, 2008)
Simulium lobatoi was described by Luna Dias et al. (2004) based on six biting females and 30 females and seven males, all reared, collected in the states of Mato Grosso and Goiás, Brazil. The larva was not described, and the authors stated that the adults and pupa of S. lobatoi were morphologically related to species within Hemicnetha Enderlein and Trichodagmia Enderlein. However, they refrained from assigning this species to any known subgenus of Neotropical Simuliidae.